Status of internet of things in the University of the Philippines Diliman Main Library - Enriquez, Neil Mark O. (2016)
The study aimed to address the Status of Internet of Things in the University of the Philippines Diliman Main Library, by assessing the status, technology integration and student knowledge on IOT. It was necessary to address the problem due to the promising effects of disruptive technologies.